A critical analysis on the response of macroinvertebrate communities along disturbance gradients: description of MEDOCC (MEDiterranean OCCidental) index. (24th March 2014) - Pinedo, Susana; Jordana, Esther; Ballesteros, Enric
Abstract Macroinvertebrate communities inhabiting shallow sandy bottoms from Catalonia and Balearic Islands coastal waters (Western Mediterranean) were used to develop the Mediterranean Occidental (MEDOCC) index, a new methodology to assess the ecological status (ES) according to Water Framework Directive (WFD) requirements. The dominance pattern of four ecological groups (EG; sensitive, indifferent, tolerant and opportunistic organisms) was studied along a disturbance gradient. Sensitive taxa were present in disturbed situations and tolerant species were related to opportunistic taxa. The thresholds between ES were scaled according to the shifts in the dominance pattern of the EGs. The distribution of the EGs along the gradient of disturbance may vary depending on the studied communities, thus influencing the boundaries defining the ES. With the development of the MEDOCC index it is shown that analysing the response of the communities to the increasing gradient of disturbance is critical to enable an accurate proposal for boundary setting to be made, and to improve the applicability of the indices. AMBI (AZTI Marine Biotic Index), Bentix (Biotic Index), and MEDOCC indices were applied to the dataset to compare the ES obtained.